Control of ventilation in humans following intermittent hypoxia - Sheel, A. W.; MacNutt, M. J. (Applied Physiology, Nutrition, and Metabolism, 2008)
Abstract: Exposure to chronic or intermittent hypoxia produces alterations in the ventilatory response to hypoxia. These adaptations can differ depending on the severity of the hypoxic stimulus, its duration, its pattern, and the presence or absence of other chemical stimuli. As such, there are significant differences between the responses to intermittent versus continuous hypoxia. Intermittent hypoxia (IH) has been shown to elicit significant changes in the peripheral chemoresponse, but the functional implications of these changes for resting and exercise ventilation are not clear. We summarize the impact of IH on resting chemosensitivity and discuss the use of IH to better understand ventilatory control during exercise. We also suggest future directions for this relatively young field, including potential clinical applications of IH research.